LncRNA MALAT1 Affects Mycoplasma pneumoniae Pneumonia via NF-κB Regulation - Gu, Haiyan; Zhu, Yifan; Zhou, Yao; Huang, Tianyu; Zhang, Siqing; Zhao, Deyu; Liu, Feng (Frontiers in Cell and Developmental Biology, 2020)
Our aim was to determine whether the long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is involved in Mycoplasma pneumoniae pneumonia (MPP), and its possible mechanism of action. MALAT1 expression in the bronchoalveolar lavage fluid of 50 hospitalized children with MPP was compared to its expression in 30 children with intrabronchial foreign bodies. MALAT1 expression was higher in children with MPP, accompanied by increased inflammatory mediators interleukin 8 (IL-8) and tumor necrosis factor alpha (TNF-α), compared to the controls. In human airway epithelial cells infected with wild-type Mycoplasma pneumoniae (strain M129), MALAT1, IL-8, and TNF-α expression significantly increased, and increased expression of IL-8 and TNF-α could be suppressed by MALAT1 knockdown. Luciferase reporter gene assay and western blot showed that knockdown of MALAT1 reduced nuclear factor-κB (NF-κB) activation. In vivo, RNAi packaged with adenovirus (AdV) was nasally transfected into BALB/c mice to silence MALAT1, and an MP-infected mouse pneumonia model was prepared. The results demonstrated that the degree of pulmonary inflammatory injury, vascular permeability, secretion of inflammatory factors, and expression of phosphorylated p65 (pp65) in MP-infected mice were partly reversed after MALAT1 knockdown compared to those in the controls. In conclusion, MALAT1 is involved in the regulation of airway and pulmonary inflammation caused by MP infection via NF-κB regulation.